Quantifying bubble-mediated transport by ebullition from aquatic sediments - Schwarz, Michael; Marcon, Lediane; Lorke, Andreas (Frontiers in Earth Science, 2023)
The widespread release of gas bubbles from aquatic sediments (ebullition) has been receiving growing scientific interest because of its globally relevant contribution to methane emissions. Besides being an efficient transport pathway for methane and other gases to the atmosphere, these bubbles have the potential to mobilize resources and pollutants previously buried in the sediment by carrying solutes and particles on their surface. The phenomenon of bubbles transporting substances other than gases is well studied in open water and widely used in technical applications, such as froth flotation or dissolved air floatation. Research on the transport capabilities of natural bubbles forming in, and being released from, aquatic sediments is exceedingly rare. Ebullition resulting from biogenic gas production in sediments is characterized by large spatial and temporal variability and bubble sizes exceed those typically used in technical applications. Here we summarize the current state of research concerning bubble mediated transport (BMT) from aquatic sediments and develop a perspective based on these findings and own experimental results. We present measurements from a shallow reservoir to explore methods to monitor BMT and gather data on ebullition over one year. We found consistent bubble size spectra, despite large temporal variations of ebullition fluxes. We highlight some of the inherent difficulties of research in this area and argue that more experiments are needed for improving empirical and mechanistic understanding of BMT.